2012
DOI: 10.1080/15389588.2011.633136
|View full text |Cite
|
Sign up to set email alerts
|

Road Traffic Injuries in Kenya: The Health Burden and Risk Factors in Two Districts

Abstract: This study highlights the significant burden of RTIs in Kenya. A renewed focus on addressing this burden is necessary. Focusing on increasing helmet and reflective clothing use and enforcement of speed limits has the potential to prevent a large number of road traffic crashes, injuries, and fatalities. However, it is difficult to demonstrate the magnitude of the injury problem to policymakers with minimal or inaccurate data, and this study illustrates the need for national continuous, systematic, and sustainab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
65
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(71 citation statements)
references
References 7 publications
(10 reference statements)
5
65
0
Order By: Relevance
“…Other causes included low visibility and technical problem. In Kenya, a recent observational study on road safety status showed that 34 % of RTA were caused by high speed in Naivasha municipality, Nakuru County, whereas a higher proportion (69 %) was found in Thika area [9]. In our study, over speeding was implicated in the occurrence of nearly one-third (32 %) of RTA events.…”
Section: Discussionmentioning
confidence: 62%
“…Other causes included low visibility and technical problem. In Kenya, a recent observational study on road safety status showed that 34 % of RTA were caused by high speed in Naivasha municipality, Nakuru County, whereas a higher proportion (69 %) was found in Thika area [9]. In our study, over speeding was implicated in the occurrence of nearly one-third (32 %) of RTA events.…”
Section: Discussionmentioning
confidence: 62%
“…Moreover, in LMICs, deaths from RTIs are actually increasing, especially among pedestrians and motorcyclists. This has been estimated to be due to increased motorization, combined with poorly organized traffic environments, and weakly enforced traffic legislation (Bachani et al 2012;Mohan, 2002;Odero 2010;Zimmerman et al 2012). From this, we can conclude that not only are injuries a significant problem worldwide, they might also be an increasing problem in LMICs.…”
Section: Introductionmentioning
confidence: 87%
“…For instance when considering reducing RTIS, strategies include: policies aimed at reducing speeds, separating pedestrians from vehicle traffic, or enforcing the use of helmets and reflective clothing (Bachani et al 2012). A meta-analysis from four studies found that helmet use for motorcyclists reduced the risk of fatal crashes by approximately 42% (Liu et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Apart from emotional losses, financial losses such as hospital costs and costs of the funeral and blood money and costs related to vehicle smoothing, painting and repairs are imposed on the driver or his family in any accident or incident. These figures will be a large amount in each year (15,(47)(48)(49)(50)(51)(52). According to the study by Ainy and colleagues (2014) (2), it was estimated that the costs resulting from RTIs include 6.46 percent of the gross domestic product (GDP) in Iran with some costs not probably included in these calculations.…”
Section: Discussionmentioning
confidence: 99%
“…Like other kinds of injuries, RTIs have high prevalence and burden of disease in LMIC (15,16). As in other LMIC, in Iran RTIs are one of the serious public health problems (17).…”
Section: Introductionmentioning
confidence: 99%